Gendering the Anthropocene ? - Achella, Stefania (Itinerari, 2023)
The essay aims to analyze the relationship between new feminist thinking and the Anthropocene. Although many feminist thinkers point out the risks and difficulties hidden behind the reference to a generic Anthropos in the expression “Anthropocene,” feminism has made important contributions to the birth of ecological sensitivity and continues to provide valuable input in attempts to rethink the relationship between human beings, non-humans and the planet. While reviewing in particular some of the most recent trends within feminism, which have tried to imagine new forms of relationship between the human and the non-human based on the principles of recognition and justice, the essay also discusses the materialistic orientation and its potential in addressing issues related to the Earth and all its inhabitants.